CREATIVITY SPECIFIC OF FUTURE ENGINEERS DEVELOPMENT IN THE PROCESS OF PROFESSIONAL COMPETENCE FORMATION - Демченко, Н. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2013)
The article deals with theoretical and methodological preconditions of structure and level of modern professional culture of future engineers at higher educational establishment in Ukraine. The role of engineering creativity in the process of present-day specialist individual and professional development was determined